INKLYUZIV TÁLIMDE KITAPQUMARLÍQ MÁDENIYATÍN RAWAJLANDÍRÍWDÍŃ PEDAGOGIKALÍQ TIYKARLARÍ - Pirniyazova, G.N.; Bektursinova, G.J. (SCIENCE and SOCIETY, 2025)
The professional skills and cooperation of teachers in the inclusive education system are primarily related to the specifics of working with children with special needs. From this perspective, improving reading culture among children with disabilities is one of the pressing issues of today. The article discusses the formation of library culture among students in inclusive education.